The Determined of Relationship Between Team Cohesion and Effective Communication Skill Levels in Volleyball Players - Kaan Karakuş; Burkay Cevahircioğlu; Ebru Şenel (Selcuk University, 2022)
The aim of this research is the determined of relationship between team cohesion and effective communication skill levels in volleyball players. In the study, a descriptive relational survey model was used. The study group consists of 193 athletes, as 143 females and 50 males. For the " Group Environment Questionnaire,", " Scale for Effective Communication in Team Sports" and personal information form were used as data collection tools. In the analysis phase; it was determined that the data showed normal distribution, Independent Sample T-Test, One-Way Analysis of Variance (ANOVA) test was applied for comparisons between groups. The relationship between Group Environment and Effective Communication levels was determined by Pearson's Analysis. The analysis results showed that; there was no significant difference according to gender, position and year of sport in the Group Environment Questionnaire. There was significant difference according to marital status in the Group Environment-Task. In the Scale for Effective Communication in Team Sports; There was no significant difference according to gender and position. There was significant difference found according to age and marital status variable in the effective communication. There was significant difference according to year of sport in discrimination-negative conflict scores. As a result of the correlation analysis, there was a positive and moderate relationship between team cohesion with effective communication. However, it was determined that there was no significant correlation between team cohesion and sub-dimension scores and discrimination-negative conflict scores. In this regard, it is foreseen that the cooperation of club technical members-athlete and including in-club social activities will be a supportive factor.